Analysis of Increasing Education Quality by Empowering the Community at SMP Islam Annizam Medan - Monica Mulyani Batubara; Yuslinda Yuslinda; Rokiba Hasibuan; Nani Rahmawati; Eva Juliana Ritonga (Edumaspul: Jurnal Pendidikan, 2022)
This study aims to: 1) Know the school principal's strategy in empowering the community to improve school quality 2) Know the role and collaboration of school principals and committees in improving the quality of education 3) Know the Empowerment of School Committees in improving the quality of education at SMP Islam Annizam Medan 4) Knowing Supporting and inhibiting factors in improving the quality of education at SMP Islam Annizam Medan. The method used in this study is a qualitative method. The technique used in analyzing the data is to record data from interviews and observations. The findings of this study are as follows: 1) So that the empowerment of school committees, especially in terms of improving the quality of school education, has not taken place as expected, the empowerment efforts are only temporary in nature; 2) The cooperative relationship between the school principal and the committee is going well, meaning that no problems arise so that the two have a harmonious relationship and 3) Supporting factors in efforts to empower school committees in improving the quality of education are carried out by the principal in efforts to maximize the functions and duties of school committees.